Near-Surface-Mounted CFRP Ropes as External Shear Reinforcement for the Rehabilitation of Substandard RC Joints - George Kalogeropoulos; Georgia Nikolopoulou; Evangelia-Tsampika Gianniki; Avraam Konstantinidis; Chris Karayannis (Buildings, 2025)
The effectiveness of an innovative retrofit scheme using near-surface-mounted (NSM) X-shaped CFRP ropes for the strengthening of substandard RC beam–column joints was investigated experimentally. Three large-scale beam–column joint subassemblages were constructed with poor reinforcement details. One specimen was subjected to cyclic lateral loading, exhibited shear failure of the joint region and was used as the control specimen. The other specimens were retrofitted and subsequently subjected to the same history of incremental lateral displacement amplitudes with the control subassemblage. The retrofitting was characterized by low labor demands and included wrapping of NSM CFPR-ropes in the two diagonal directions on both lateral sides of the joint as shear reinforcement. Single or double wrapping of the joint was performed, while weights were suspended to prevent the loose placement of the ropes in the grooves. A significant improvement in the seismic performance of the retrofitted specimens was observed with respect to the control specimen, regarding strength and ductility. The proposed innovative scheme effectively prevented shear failure of the joint by shifting the damage in the beam, and the retrofitted specimens showed a more dissipating hysteresis behavior without significant loss of lateral strength and axial load-bearing capacity. The cumulative energy dissipation capacity of the strengthened specimens increased by 105.38% and 122.23% with respect to the control specimen.